Molecular dynamics simulation of hydrogen diffusion into brine: Implications for underground hydrogen storage - Kalati, Seyedeh Saba; Pour Khiabani, Nahid; Ayatollahi, Shahab; Mahani, Hassan; Zivar, Davood; Esmaeilbeig, Mohammad Amin (International journal of hydrogen energy, 2024)
Underground hydrogen storage has been the subject of extensive research recently. Hydrogen diffusion coefficient into brine critically affects hydrogen loss. However, the available data pertain to hydrogen diffusivity in pure water or NaCl solutions, with rare interpretations of temperature and salinity effects. In this paper, molecular dynamics simulations at realistic conditions were conducted to calculate these coefficients in various brines, particularly those containing divalent salts. The results indicate lower diffusivities at higher salinities and lower temperatures, the value being 7.29 × 10−9 m2/s at 323 K, increasing to 10.2 × 10−9 m2/s at 353 K for 1 molal NaCl solution. The diffusion coefficient decreases up to 38 % as the salinity increases from 1 to 5 molal. Besides, hydrogen diffusivity in MgCl2 solution is up to 60 % smaller than in NaCl solutions at the same molality. Radial distribution functions and hydrogen bond analyses confirm the results. This research provides new data for estimating hydrogen loss in aquifers or water-saturated caprocks. [Display omitted] •The diffusion coefficient of hydrogen in brine is calculated at actual UHS conditions.•The simulation results are validated using literature data.•The impacts of salinity and temperature on the diffusivities are evaluated.•The hydrogen diffusivity in MgCl2 and NaCl solutions are compared.•A mathematical model to predict hydrogen diffusivity in NaCl solution is presented.